2015
DOI: 10.5433/1679-0359.2015v36n5p3257-3268
|View full text |Cite
|
Sign up to set email alerts
|

Análise do efeito da colheita da planta de milho em diferentes estádios reprodutivos e do processamento dos grãos sobre a qualidade da silagem

Abstract: <p>O experimento foi conduzido no Núcleo de Produção Animal (NUPRAN) da Universidade Estadual do Centro Oeste (UNICENTRO), com o objetivo de avaliar o efeito da colheita da planta de milho em diferentes estádios reprodutivos e com diferentes processamentos de grãos sobre a digestibilidade da matéria seca, digestibilidade da fibra em detergente neutro e desempenho animal. O delineamento experimental foi inteiramente casualizado, composto por 4 tratamentos com 4 repetições, onde cada repetição constou de u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This can be attributed to the greater participation of grains with the increase in the cutting height as reported by Vaz et al (10) . Marafon et al (22) concluded that the greater participation of grains in ensiled mass allows better transformation of consumed DM into meat, in addition to improving carcass characteristics (23) .…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the greater participation of grains with the increase in the cutting height as reported by Vaz et al (10) . Marafon et al (22) concluded that the greater participation of grains in ensiled mass allows better transformation of consumed DM into meat, in addition to improving carcass characteristics (23) .…”
Section: Resultsmentioning
confidence: 99%